Investigating the role of structural water on the electrochemical properties of α-V2O5 through density functional theory. Issue 39 (29th September 2022) - Sandagiripathira, Kaveen; Moghaddasi, Mohammad Ali; Shepard, Robert; Smeu, Manuel
Abstract : Structural water was found to affect the voltage, energy density, and diffusion properties of α-V2 O5 through increased interlayer spacing and charge shielding effects when intercalating mono-, di-, and trivalent ions for secondary batteries. Abstract : The α polymorph of V2 O5 is one of the few known cathodes capable of reversibly intercalating multivalent ions such as Mg, Ca, Zn and Al, but suffers from sluggish diffusion kinetics. The role of H2 O within the electrolyte and between the layers of the structure in the form of a xerogel/aerogel structure, though, has been shown to lower diffusion barriers and lead to other improved electrochemical properties. This density functional theory study systematically investigates how and why the presence of structural H2 O within α-V2 O5 changes the resulting structure, voltage, and diffusion kinetics for the intercalation of Li, Na, Mg, Ca, Zn, and Al. We found that the coordination of H2 O molecules with the ion leads to an improvement in voltage and energy density for all ions. This voltage increase was attributed to the extra host sites for electrons present with H2 O, thus leading to a stronger ionization of the ion and a higher voltage. We also found that the increase in interlayer distance and a potential "charge shielding" effect drastically changes the electrostatic environment and the resulting diffusion kinetics. For Mg and Ca, this resulted in a decrease in diffusion barrier from 1.3 eV and 2.0 eV to 0.89 eV and 0.4 eV, respectively. We hope that our study motivates similar research regarding the role of water in both V2 O5 xerogels/aerogels and other layered transition metal oxides.